Phenotypic and functional characteristics of murine CD11c+ B cells which is suppressed by metformin - Ramirez De Oleo, Ivan; Kim, Vera; Atisha-Fregoso, Yemil; Shih, Andrew J.; Lee, Kyungwoo; Diamond, Betty; Kim, Sun Jung (Frontiers in Immunology, 2023)
Since the description of age-associated or autoimmune-associated B cells (ABCs), there has been a growing interest in the role of these cells in autoimmunity. ABCs are differently defined depending on the research group and are heterogenous subsets. Here, we sought to characterize ABCs in Sle1/2/3 triple congenic (TC) mice, which is a well accepted mouse model of lupus. Compared to follicular (FO) B cells, ABCs have many distinct functional properties, including antigen presentation. They express key costimulatory molecules for T cell activation and a distinct profile of cytokines. Moreover, they exhibit an increased capacity for antigen uptake. ABCs were also compared with germinal center (GC) B cells, which are antigen activated B cell population. There are several phenotypic similarities between ABCs and GC B cells, but GC B cells do not produce proinflammatory cytokines or take up antigen. While T cell proliferation and activation is induced by both FO B and ABCs in an antigen-dependent manner, ABCs induce stronger T cell receptor signaling in naïve CD4+ T cells and preferentially induce differentiation of T follicular helper (Tfh) cells. We found that ABCs exhibit a distinct transcriptomic profile which is focused on metabolism, cytokine signaling and antigen uptake and processing. ABCs exhibit an increase in both glycolysis and oxidative phosphorylation compared to FO B cells. Treatment of ABCs with metformin suppresses antigen presentation by decreasing antigen uptake, resulting in decreased Tfh differentiation. Taken together, these findings define a fundamental connection between metabolism and function within ABCs.